2008
DOI: 10.1021/cg800487b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonded Networks Constructed with 5-Nitrobarbiturate

Abstract: A series of nine compounds including tetra-alkylammonium 5-nitrobarbiturates and their urea and thiourea adducts have been obtained and characterized by single crystal X-ray analysis. The hydrogen-bonded networks in these compounds feature three different kinds of dimeric 5-nitrobarbiturate linkages (para-to-para, ortho-to-ortho and para-to-ortho), which are stabilized by formation of the cyclic urea dimer supramolecular synthon. In four thiourea complexes, the 5-nitrobarbiturate dimer is the dominant building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…[32][33][34] Once, it was established that the strength of any hydrogen bond depends more on donor acidity than on acceptor basicity, 35,36 thioureas having stronger hydrogen bond donating ability, 37 emerged as equally attractive and robust supramolecular synthons in crystal engineering. 34,[38][39][40][41][42][43] In fact, a comparative study of structurally similar urea and thiourea derivatives showed the latter to have a larger dimerization constant in solution. 44 Thiosemicarbazones or N-iminothioureas can be prepared by the simple condensation reaction of aldehydes/ketones with thiosemicarbazides.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Once, it was established that the strength of any hydrogen bond depends more on donor acidity than on acceptor basicity, 35,36 thioureas having stronger hydrogen bond donating ability, 37 emerged as equally attractive and robust supramolecular synthons in crystal engineering. 34,[38][39][40][41][42][43] In fact, a comparative study of structurally similar urea and thiourea derivatives showed the latter to have a larger dimerization constant in solution. 44 Thiosemicarbazones or N-iminothioureas can be prepared by the simple condensation reaction of aldehydes/ketones with thiosemicarbazides.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, being more acidic NH-donors, 42 thioureas also emerged as equally attractive and reliable supramolecular synthons in crystal engineering. 39,[43][44][45][46][47][48] In fact, a larger dimerization constant in solution has been observed for the thioureas in a comparative study of structurally similar urea and thiourea derivatives. 49 Thiosemicarbazones or N-iminothioureas are the condensation products of thiosemicarbazides and carbonyl compounds (aldehydes, ketones) that are widely studied with diverse applications in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, Whitesides and co-workers focused on the construction of soluble molecular aggregates and crystalline materials utilizing hydrogen-bonding interactions between designed derivatives of isocyanuric acid and melamine. , Later on, Reinhoudt and co-workers conducted a comprehensive study of the surface chemistry, kinetics, and supramolecular chirality of multiple rosette systems. To overcome the problem of low solubility of cyanuric acid, we decided to employ the isocyanurate monoanion in the construction of rosette structures, noting that deprotonation of one N–H group creates a hydrogen-bond accepting site. With reference to our previous studies on the construction of anionic host lattices from urea/thiourea and nitrobarbiturate, as well as the designed construction of rosette layers and linear “fused-rosette ribbon” assembled from the guanidinium cation and hydrogen carbonate dimer in a 1:1 molar ratio, , we decided to employ the urea/thiourea molecule as a “pseudo- C 3 -symmetric” molecular component to match the hydrogen-bonding sites of the isocyanurate monoanion for the generation of new types of rosette tapes or layers.…”
Section: Introductionmentioning
confidence: 99%
“…31−44 To overcome the problem of low solubility of cyanuric acid, we decided to employ the isocyanurate monoanion in the construction of rosette structures, noting that deprotonation of one N−H group creates a hydrogen-bond accepting site. With reference to our previous studies on the construction of anionic host lattices from urea/thiourea and nitrobarbiturate, 45 as well as the designed construction of rosette layers 46 and linear "fusedrosette ribbon" assembled from the guanidinium cation and hydrogen carbonate dimer in a 1:1 molar ratio, 47,48 we decided to employ the urea/thiourea molecule as a "pseudo-C 3symmetric" 49 molecular component to match the hydrogenbonding sites of the isocyanurate monoanion for the generation of new types of rosette tapes or layers.…”
Section: ■ Introductionmentioning
confidence: 99%